Vitamin delivery: Carriers based on nanoliposomes produced via ultrasonic irradiation. (June 2016) - Bochicchio, Sabrina; Barba, Anna Angela; Grassi, Gabriele; Lamberti, Gaetano
Abstract: In recent years much attention has been focused on using lipid carriers as potential delivery systems for bioactive molecules due to their favorable properties such as high biocompatibility, size and composition versatility. In this paper formulation, preparation and characterization of liposomes, a class of powerfully versatile lipidic carriers, produced by means of an innovative ultrasound-assisted approach based on the thin-film hydration method, are presented and discussed. The main aim of this study is to obtain nanostructures (Small Unilamellar Vesicles, SUVs), less than 100 nm in size, loaded with different vitamins (B12, tocopherol and ergocalciferol), starting from lipidic microstructures (Multilamellar Large Vesicles, MLVs). Suitable formulations, sonication protocols and nanoliposomes were pointed out. SUVs with diameter size ranging from 40 nm to 51 nm were achieved starting from MLVs with a diameter range of 2.9–5.7 μm. Starting from MLVs with higher encapsulation efficiency for all kind of vitamins, SUVs with an encapsulation efficiency of 56% for vitamin B12, 76% for α-tocopherol and 57% for ergocalciferol were obtained. Stability tests have shown that the used lipid composition allows to keep intact the nanovesicles and their content for more than 10 days if incubated at simulated extracellular environment conditions. Highlights: Nanoliposomes with high vitamins loadings can be used to boost bioactive nutrient delivery. Liposome-based vitamin delivery systems offer many advantages due to manly their biocompatibility. Ultrasonic treatments were used in size reduction of liposomal large structures.